Penyelesaian Sengketa Perdata dalam Transaksi E-Commerce melalui Online Dispute Resolution - Putri Verisca Salsabila; Febriansyah, Ferry Irawan; Isnandar, Aries (Lembaga Teewan Journal Solutions, 2026)
The exponential growth of E-Commerce in Indonesia has not only boosted the economy but also increased the potential for civil disputes that are cross-border, low-value, and digital-evidence based. Conventional dispute resolution mechanisms are deemed inadequate due to slow procedures, high costs, and misalignment with the nature of digital transactions. Therefore, this study aims to analyze the effectiveness of Online Dispute Resolution (ODR) as an alternative solution. Using a normative legal research method, this study examines the gaps in national regulations (ITE Law, Arbitration Law, Consumer Protection Law) in accommodating ODR, and compares best practices from the European Union, Singapore, and China. The results identify multidimensional implementation challenges, covering legal aspects (legitimacy and enforcement of ODR outcomes), technical aspects (cybersecurity, infrastructure), and socio-cultural aspects (digital divide, literacy). In conclusion, this study recommends the development of an integrated hierarchical ODR model, starting from automated mechanisms on E-Commerce platforms, certified independent ODR, to integration with electronic courts. Policy recommendations focus on three pillars: the establishment of explicit umbrella regulations, the formation of a supervisory authority, and the improvement of public capacity and digital literacy. A comprehensive ODR implementation is believed to restore trust and create a fair and sustainable E-Commerce ecosystem.